Zakat Distribution sebagai Moderasi Pengaruh Gross Domestic Product (GDP) Terhadap Tingkat Kemiskinan di Indonesia - Yeti Meliany Lubis; Eva Yuniarti Utami; Imron Natsir; Ramli Semmawi; Fahmi Syam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of Gross Domestic Product (GDP) on the poverty rate in Indonesia with zakat distribution as a moderating variable. The research method used in this study is quantitative descriptive research with secondary data types that can be accessed through the website of the Central Statistics Agency (BPS) of Indonesia and the page of the PPID Baznas RI Information and Documentation Management Officer. Data analysis was carried out using the Eviews 12 application to determine the effect of Gross Domestic Product on the poverty rate in Indonesia. Then a Moderated Regression Analysis (MRA) test was carried out to determine the moderating effect of zakat distribution on the relationship between Gross Domestic Product and the poverty rate in Indonesia. The results of this study are that Gross Domestic Product does not have a significant effect on the poverty rate in Indonesia. Therefore, the moderation test conducted shows that zakat distribution does not directly moderate the relationship between gross domestic product and poverty rates in Indonesia.